Investigation on the novel measurement for fabric wrinkle simulating actual wear. Issue 2 (1st February 2017) - Liu, Chengxia
Abstract: It is very important to measure fabric wrinkling objectively and accurately. However, the most commonly used measurements could not be employed to realistically evaluate and predict how fabric will resist wrinkle when worn on human body. In our previous study, an equipment of measuring fabric wrinkling that can simulate actual wear was proposed. In this paper, we conduct further investigation on the measurement for fabric wrinkle-simulating actual wear, including improving the equipment, validating its repeatability, and clarifying its more accurate relationship with the wrinkle recovery angle (WRA) method. Results show that the measuring repeatability of the method is much better than WRA method and fabric wrinkling in the warp and bias direction plays more important part than weft. Therefore, it is advisable that WRA of the bias should be increased, whose measurement stability is the best in the WRA method as well. Equations of Wrinkle Density (WD) with WRAs are established, which can be used to estimate wrinkling of clothes after actual wear only by several WRAs of fabrics, avoiding the tedious clothes making and trial work.